Combining eddy current, thermography and laser scanning to characterize low-velocity impact damage in aerospace composite sandwich panels. (June 2021) - Rellinger, T.; Underhill, P.R.; Krause, T.W.; Wowk, D.
Abstract: Aerospace sandwich panels subject to low-velocity impacts can develop damage in both the face sheet and the core that may compromise structural integrity. The standard repair manual for each aircraft specifies allowable damage limits that consider surface dents and the presence of disbonds or delaminations. A strategy for identifying the types of impact damage according to the standard repair manual using a series of non-destructive inspection techniques is presented for honeycomb sandwich panels with composite facesheets and metallic core. Eddy current is first used to identify impact sites, followed by thermography to detect disbonds or delaminations and laser scanning to measure the size of surface dents. Images of damage sites in honeycomb sandwich panels from low-velocity impacts created using a drop tower show that when used together, these inspection methods are able to detect and distinguish between three different damage configurations; core crush, surface dents, and adhesive disbonds or face sheet ply delaminations. While these three methods are commonly used non-destructive evaluation techniques, this paper focuses on their combined use in identifying different types of impact damage in aerospace sandwich panels in-situ according to the requirements of the standard repair manual. The combined methods are shown to address requirements of dent depth, dent area, and the identification of disbonds or delaminations in a more rapid, repeatable and robust manner than is currently employed.